Addressing the phytochemical prospection of thermally treated Eucalyptus grandis wood (Research, Society and Development, 2020)
This work aimed to investigate phytochemical prospection in treated and untreated wood of Eucalyptus grandis to understand the dynamics of extractives in relation to heat treatment. Samples of E. grandis wood were collected and grouped into external and internal regions. Half of the samples from each region were submitted to heat treatment at 190 ºC. From the treated and untreated samples, phytochemical tests were performed to detect classes of metabolites present in the E. grandis raw wood, hydrophilic extract and lipophilic extract. Phytochemical analysis detected the presence of alkaloids, phenolic compounds and triterpenoids in all hydrophilic extracts of the studied species.  Presence of flavanonols, flavanones and saponins was detected only in the internal region of the wood. Tannins, leucoanthocyanidins, triterpenoids and saponins were influenced by heat treatment. The classes of flavonoids, xanthones and alkaloids are the most resistant to heat treatment. The phytochemical analysis made it possible to identify a new class of extractives that emerged after heat treatment, flavones.